An injectable thermosensitive hydrogel with a self-assembled peptide coupled with an antimicrobial peptide for enhanced wound healing. Issue 32 (4th August 2022) - Feng, Tianqi; Wu, Hongyan; Ma, Wendi; Wang, Zhaoguo; Wang, Chunli; Wang, Yilong; Wang, Siyao; Zhang, Mei; Hao, Linlin
Abstract : PNI/RA-Amps is an injectable thermo-reversible dressing triggered by body temperature, and exhibits a rapid reversible sol–gel–sol transition of ∼23 s. MGF E peptide was loaded into the hydrogel to enable bacteriostasis, hemostasis and wound healing. Abstract : A wound dressing based on a thermosensitive hydrogel shows advantages over performed traditional dressings, such as rapid reversible sol–gel–sol transition properties and the capacity to fill an irregular-shaped wound area. Herein, RA-Amps was fabricated by coupling a self-assembled peptide RADA16 with an antibacterial peptide (Amps) and incorporated into a PNIPAM hydrogel containing an MGF E peptide to develop a multi-functional composite hydrogel with thermo-response properties, good biocompatibility, good mechanical properties, and antibacterial and carrier functions for wound healing. PNI/RA-Amps is an injectable thermo-reversible system with a phase transition temperature of ∼32 °C, and exhibits a rapid reversible sol–gel–sol transition of ∼23 s, which makes it conducive to sealing the wound area and avoiding sol diffusion caused by a lengthy gel time. MGF E peptide was loaded into a hydrogel and released continuously to promote fibroblast proliferation. Rat full-thickness skin experiments revealed that the PNI/RA-Amps/E hydrogel accelerates wound healing significantly by accelerating epithelialization, the generation of new blood vessels and promoting the generation of collagen fiber compared with commercial dressing. Thus, our findings establish a new candidate for use as an injectable wound dressing for the clinical treatment of wounds.